Banyu Atirodra: Transformasi Air Dalam Wujud Tari Kekebyaran - Gunawan, Kadek Putra Dharma; Sulistyani, Sulistyani; Gunarta, I Wayan Adi (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
Banyu Atirodra Dance is a dance that takes creative sources from the Siat Yeh cultural event in Banjar Teba, Jimbaran, Badung Regency. Siat Yeh can be divided into two words, siat means war and yeh means water. So Siat Yeh is a war that uses water as its weapon. In the creation of the Banyu Atirodra Dance, the creator made the use of water in this tradition as the basic capital and the trigger for choreographic ideas. Banyu means water and Atirodra means terrible, so Banyu Atirodra is the awesomeness of water that is able to provide prosperity as well as bring harm to humans. In the process of its creation, the creators collaborated with the Bumi Bajra Sandhi Foundation in the Merdeka Belajar-Kampus Merdeka program by taking the form of independent study/project learning.The creation of Banyu Atirodra Dance uses the method of creating Angripta Sasolahan (creating dances) by I Kt. Suteja in the book Catur Asrama Pendakian Spiritual Masyarakat Bali Dalam Sebuah Karya Tari. This book describes the five stages of creation, including ngarencana (planning), nuasen (prayer procession), makalin (improvisation), nelesin (formation) and ngebah (premier performance). The Banyu Atirodra dance is a subtle male dance (kekebyaran) performed in groups with the dance structure consisting of four parts that last 11 minutes. The dance music uses Gamelan Gong Kebyar components such as gong, klenong, kajar, kecek, kendang and flutes. Using minimalist (natural) make-up with white nuances, consisting of white trousers, white belt (stagen), don girang and white kancut (lelancingan). The creator hopes that the values contained in this work can be implemented in social life, especially in the use of water which is very crucial for life